Bcl-xL in neuroprotection and plasticity - Jonas, Elizabeth A.; Porter, George A.; Alavian, Kambiz N. (Frontiers in Physiology, 2014)
Accepted features of neurodegenerative disease include mitochondrial and protein folding dysfunction and activation of pro-death factors. Neurons that experience high metabolic demand or those found in organisms with genetic mutations in proteins that control cell stress may be more susceptible to aging and neurodegenerative disease. In neurons, events that normally promote growth, synapse formation and plasticity are also often deployed to control neurotoxicity. Such protective strategies are coordinated by master stress-fighting proteins. One such specialized protein is the anti-cell death Bcl-2 family member Bcl-xL, whose myriad death-protecting functions include enhancement of bioenergetic efficiency, prevention of mitochondrial permeability transition channel activity, protection from mitochondrial outer membrane permeabilization to pro-apoptotic factors, and improvement in the rate of vesicular trafficking. Synapse formation and normal neuronal activity provide protection from neuronal death. Therefore Bcl-xL brings about synapse formation as a neuroprotective strategy. In this review we will consider how this multi-functional master regulator protein uses many strategies to enhance synaptic and neuronal function and thus counteracts neurodegenerative stimuli.